Effect of Oxalic Acid and Humic Acid on the Species Distribution and Activity of Fluoride in Soil - Chen, Wen; Pang, Xiao-Feng; Li, Jing-Hui; Hang, Xing (Asian Journal of Chemistry, 2012)
In order to study the effect of oxalic acid and humic acid on the acidity and transformation law of fluoride in high fluoride-contained soil, the tropic Zhu Jiang delta soil sample (fluvo-aqui soil and paddy soil) was investigated by the test method using polarography while sequential extraction was conducted to extract fluoride of various species in the original soil sample and the cultivated soil sample respectively. The result indicates that the oxalic acid concentration being over 0.02 mmol/g, oxalic acid has great influence on the soil pH value and the content of water soluble fluoride (Ws-F), exchangeable fluoride (Ex-F) and fluoride bond to Fe/Mn oxides (Fe/Mn-F); the acidity of the two soils decreases. The content of fluoride of other species increases significantly. While the content of humic acid at an appropriate concentration range (£1.514 mg/g) leads to the decrease of water soluble fluoride and fluoride bond to Fe/Mn oxides and the increase of exchangeable fluoride. This paper concludes, compared with high-molecular-weight organic acid, low-molecular-weight organic acid can activate fluoride in soil more easily, which in turn induces more fluoride intake by crops. Fluoride bound to organic matter (Or-F) is not discussed as its content is lower than the blank solution.